Environmental Factors Driving the Seasonal Dynamics of Ixodes ricinus and Dermacentor reticulatus in Eastern Poland - Aneta Woźniak; Zbigniew Zając; Joanna Kulisz (Insects)
I. ricinus and D. reticulatus are among the most important vectors of pathogens causing tick-borne diseases in humans and animals. This study investigated their seasonal activity in Eastern Poland, a region with one of the highest incidence rates of tick-borne diseases nationwide. Additionally, we examined tick habitat preferences and the impact of abiotic factors on their activity patterns. To this end, we conducted systematic monitoring of tick activity between 2017 and 2019 in two ecologically distinct habitats: a mixed forest and a meadow. Using Generalized Additive Models (GAMs) and Generalized Linear Mixed Models (GLMMs), we analyzed the collected data. Our findings indicate that I. ricinus reaches peak activity in late spring, within a temperature range of 9.5–16.5 °C and relative humidity between 45.3% and 84.5%. In contrast, D. reticulatus demonstrated a broader thermal tolerance, remaining active at temperatures ranging from 1.0 °C to 32.6 °C and relative air humidity of 33.8–89.0%. Both temperature and humidity were found to be significant factors influencing tick activity. Moreover, I. ricinus and D. reticulatus exhibited distinct seasonal activity patterns throughout the year.